Kv3.1 channels stimulate adult neural precursor cell proliferation and neuronal differentiation. (12th April 2013) - Yasuda, Takahiro; Cuny, Hartmut; Adams, David J.
Key points: In the adult mammalian brain, neural precursor cells (NPCs) play an important role in neuronal plasticity. Although adult NPCs exhibit voltage‐gated, delayed rectifier K + (KDR ) channel currents, the KDR channel subtype dominantly expressed in adult NPCs and its functional role have not been defined. Using gene knockdown targeting Kv 3.1 K + channels, we show Kv 3.1 is a dominant KDR subtype expressed in adult NPCs. Kv 3.1 knockdown significantly decreased adult NPC proliferation and reduced differentiation into neuroblasts. Our findings provide new insight into a mechanism of adult neurogenesis and suggest that selective activation of Kv 3.1 in adult NPCs may be a new therapeutic approach to treating neurodegenerative diseases. Abstract Adult neural stem/precursor cells (NPCs) play a pivotal role in neuronal plasticity throughout life. Among ion channels identified in adult NPCs, voltage‐gated delayed rectifier K + (KDR ) channels are dominantly expressed. However, the KDR channel subtype and its physiological role are still undefined. We used real‐time quantitative RT‐PCR and gene knockdown techniques to identify a major functional KDR channel subtype in adult NPCs. Dominant mRNA expression of Kv 3.1, a high voltage‐gated KDR channel, was quantitatively confirmed. Kv 3.1 gene knockdown with specific small interfering RNAs (siRNA) for Kv 3.1 significantly inhibited Kv 3.1 mRNA expression by 63.9% ( P < 0.001) and KDR channel currents by 52.2% ( P < 0.001). This indicates that Kv 3.1 is the subtype responsible for producing KDR channel outward currents. Resting membrane properties, such as resting membrane potential, of NPCs were not affected by Kv 3.1 expression. Kv 3.1 knockdown with 300 nm siRNA inhibited NPC growth (increase in cell numbers) by 52.9% ( P < 0.01). This inhibition was attributed to decreased cell proliferation, not increased cell apoptosis. We also established a convenient in vitro imaging assay system to evaluate NPC differentiation using NPCs from doublecortin‐green fluorescent protein transgenic mice. Kv 3.1 knockdown also significantly reduced neuronal differentiation by 31.4% ( P < 0.01). We have demonstrated that Kv 3.1 is a dominant functional KDR channel subtype expressed in adult NPCs and plays key roles in NPC proliferation and neuronal lineage commitment during differentiation.